Analisis Niat Pembelian Pada Instagram Online Shopping Menggunakan Information Acceptance Model (IACM) - Wahyutama Fitri Hidayat; Rangga Sanjaya; Ali Mustopa (LPPM Universitas Bina Sarana Informatika, 2020)
Along with the development of technology and information, it also has an impact on the product sales media, one of which is through Instagram online shopping. The results of the surf show that comments (electronic word of mount) are on Instagram online shopping. This study aims to analyze the effect of the electronic word of month (EWOM) on purchase intentions using the Information Acceptance Model (IACM) model. The method used in this research is descriptive quantitative to find out the cause and effect relationship of IACM variables. The population in this research is Instagram users who have seen product promotions through Instagram. The sampling technique used is incidental sampling by distributing questionnaires online. The data analysis technique used is multiple linear regression analysis. Based on the results of the research, it can be concluded that the electronic word of mount found on Instagram online shopping has a significant partial effect on purchase intention. This can be seen from the results of the calculation of all the t-count variables 0.191 and the significance level 0.05. Based on the results of the calculation of the determination coefficient (R2), the magnitude of the effect on the benefits of information is information quality 19.5%, information credibility 41.3%, information needs 13.9%, and attitudes towards information 28.6%. The results of information adoption are affected by 11.2% of the benefits of information. Other lts show that 24.9% of information adoption affects purchase intentions. While attitudes toward information affect 38.9% of purchase intentions.